2011
DOI: 10.1016/j.proci.2010.05.098
|View full text |Cite
|
Sign up to set email alerts
|

High pressure oxidation of C2H4/NO mixtures

Abstract: An experimental and kinetic modeling study of the interaction between C 2 H 4 and NO has been performed under flow reactor conditions in the intermediate temperature range (600-900 K), high pressure (60 bar), and for stoichiometries ranging from reducing to oxidizing conditions. The main reaction pathways of the C 2 H 4 /O 2 /NO x conversion, the capacity of C 2 H 4 to remove NO, and the influence of the presence of NO x on the C 2 H 4 oxidation are analyzed. Compared to the C 2 H 4 /O 2 system, the presence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
21
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 30 publications
4
21
0
Order By: Relevance
“…It was also observed that a significant amount of NO can participate in a recycle loop with HCNO through HCCO, especially when a significant portion of the oxidation pathway is through HCCO as discussed in Section 3.3.2. Several different groups have also observed that removal of NO can occur through reaction with HCCO and vinyl radical [39,23]. This loop is shown in reactions (11)-(15) below:…”
Section: No Formationmentioning
confidence: 92%
See 3 more Smart Citations
“…It was also observed that a significant amount of NO can participate in a recycle loop with HCNO through HCCO, especially when a significant portion of the oxidation pathway is through HCCO as discussed in Section 3.3.2. Several different groups have also observed that removal of NO can occur through reaction with HCCO and vinyl radical [39,23]. This loop is shown in reactions (11)-(15) below:…”
Section: No Formationmentioning
confidence: 92%
“…The NO x sub-mechanism includes all relevant N-containing reactions of GRI-Mech 3.0 [21], Dagaut et al [22] and Giménez-López et al [23], including mechanisms for: thermal NO, prompt NO, N 2 O, NNH, nitro-hydrocarbons, and nitroso-compounds. The prompt-initiating reaction of Fenimore [24,25] used in the GRI-Mech 3.0 shown in reaction (2) has been shown to be spin forbidden by Moskaleva and Lin [26].…”
Section: Mechanism Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…To this end, the use of chemical kinetic models has been invaluable, and in recent years there have been quite a few proposed mechanisms concerned with NO x chemistry, and with interactions of nitrogen oxides with hydrocarbons. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] However, as will be discussed, there can be significant disparity between published models in terms of the thermochemical properties of nitrogen-containing species therein.…”
Section: Introductionmentioning
confidence: 99%